2006
DOI: 10.1016/j.visres.2005.11.004
|View full text |Cite
|
Sign up to set email alerts
|

A common mechanism for perceptual filling-in and motion-induced blindness

Abstract: Perceptual-Wlling-in (PFI) and motion-induced-blindness (MIB) are two phenomena of temporary blindness in which, after prolonged viewing, perceptually salient targets repeatedly disappear and reappear, amidst a Weld of distracters (i.e., non-targets). Past studies have shown that boundary adaptation is important in PFI, and that depth ordering between target and distracter pattern is important in MIB. Here we show that the reverse is also true; that boundary adaptation is important in MIB, and that depth order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
3
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 21 publications
1
44
3
1
Order By: Relevance
“…MIB disappearances last for up to several seconds, even with high contrast, relatively large stimuli, and when located near fixation: eccentricity of 18 (Bonneh et al, 2001;Bonneh, Donner, Cooperman, Heeger, & Sagi, 2014). As for Troxler (1804) fading, the mechanisms underlying MIB was suggested to involve low-level processes such as contrast adaptation (Caetta, Gorea, & Bonneh, 2007;Gorea & Caetta, 2009), and filling-in (Hsu, Yeh, & Kramer, 2006), as well as depth ordering and surface completion (Graf, Adams, & Lages, 2002). However, recent findings show additional components in MIB related to the neural competition between the static target and the moving background (Bonneh et al, 2001;Bonneh et al, 2014;Donner, Sagi, Bonneh, & Heeger, 2008).…”
Section: Introductionmentioning
confidence: 94%
“…MIB disappearances last for up to several seconds, even with high contrast, relatively large stimuli, and when located near fixation: eccentricity of 18 (Bonneh et al, 2001;Bonneh, Donner, Cooperman, Heeger, & Sagi, 2014). As for Troxler (1804) fading, the mechanisms underlying MIB was suggested to involve low-level processes such as contrast adaptation (Caetta, Gorea, & Bonneh, 2007;Gorea & Caetta, 2009), and filling-in (Hsu, Yeh, & Kramer, 2006), as well as depth ordering and surface completion (Graf, Adams, & Lages, 2002). However, recent findings show additional components in MIB related to the neural competition between the static target and the moving background (Bonneh et al, 2001;Bonneh et al, 2014;Donner, Sagi, Bonneh, & Heeger, 2008).…”
Section: Introductionmentioning
confidence: 94%
“…The properties of MIB do not seem to reflect sensory suppression or adaptation, because the disappearances in MIB cannot be explained by local adaptation or retinal stabilization, and it also does not depend on local masking from the moving pattern [1,5] . A consensus being established is that MIB is a consequence of perceptual rivalry, in which the targets and moving pattern compete against each other in perceptual processing [6] , and only the winner enters awareness while the loser is kept out of awareness.…”
mentioning
confidence: 97%
“…They suggested that MIB resulted from the completion of the grid elements into a perceptual surface and the interactions between the grid-and targets-surface. From the perspective of perceptual rivalry, Hsu and his colleagues [3,5] gave an explanation for the effect that more salient targets (e.g. with higher contrast, or some kinds of "popout") increase rather than decrease MIB [1,3] .…”
mentioning
confidence: 99%
“…However, we informally noticed that MIB is completely eliminated by continuously moving one's eyes back and forth throughout the trial, even if these eye movements are not directed toward a target. Whereas low-level retinotopically specific adaptation is not critical to MIB (Mitroff & Scholl, 2004;Montaser-Kouhsari et al, 2004), this finding suggests that adaptation or inhibition (Gorea & Caetta, 2009;Hsu, Yeh, & Kramer, 2006) at a higher, non-retinotopically-specific level does play a crucial role. This is also suggested by the fact that MIB is never instantaneous.…”
Section: Introductionmentioning
confidence: 81%